Imidazole‐ and Benzimidazole‐Based Inhibitors of the Kinase IspE: Targeting the Substrate‐Binding Site and the Triphosphate‐Binding Loop of the ATP Site. Issue 6 (4th January 2013) - Mombelli, Paolo; Le Chapelain, Camille; Munzinger, Noah; Joliat, Evelyne; Illarionov, Boris; Schweizer, W. Bernd; Hirsch, Anna K. H.; Fischer, Markus; Bacher, Adelbert; Diederich, François
Abstract: The enzymes of the mevalonate‐independent biosynthetic pathway to isoprenoids are attractive targets for the development of new drug candidates, in particular against malaria and tuberculosis, because they are present in major human pathogens but not in humans. Herein, the structure‐based design, synthesis, and biological evaluation of a series of inhibitors featuring a central imidazole or benzimidazole scaffold for the kinase IspE from E. coli, a model for the corresponding malarial enzyme, are described. Optimization of the binding preferences of the hydrophobic sub‐pocket at the substrate‐binding site allowed IC 50 values in the lower micromolar range to be reached. Structure–activity relationship studies using a 1, 2‐disubstituted imidazole central core revealed that alicyclic moieties fit the sub‐pocket better than acyclic aliphatic and aromatic residues. The phosphate‐binding region in the ATP‐binding site of IspE, a neutral glycine‐rich loop, was addressed for the first time by an additional vector attached to the central core. Polar functional groups, such as trifluoromethyl or nitriles, were introduced to undergo orthogonal dipolar interactions with the amide groups in the loop. Alternatively, small hydrogen‐bond‐accepting heterocyclic residues, capable of binding to the convergent NH groups in the loop, were explored. The biological data showed slightly improved inhibitory potency in some cases and confirmed the challenges in addressing, with gain in binding affinity, the highly water‐exposed sections of enzyme active sites, such as the glycine‐rich loop of IspE. Abstract : Inhibitors of the kinase E . coli IspE, an enzyme involved in the synthesis of isoprenoids and a model for IspE from P . falciparum, were developed. Decorated imidazole‐ and benzimidazole‐based scaffolds address the cytidine‐binding pocket, the hydrophobic sub‐pocket, and the phosphate‐binding region in the active site. In vitro activities in the micromolar IC 50 ‐range were measured.